Pengaruh Natrium Hialuronat terhadap Penetrasi Kofein Sebagai Antiselulit dalam Sediaan Hidrogel, Hidroalkoholik Gel, dan Emulsi Gel - Djajadisastra, Joshita; Dzuhro, Zuraida Syafara; Sutriyo, Sutriyo (UI Scholars Hub, 2014)
Anticellulite topical gel preparation with caffeine as active ingredient needs a penetration enhancer to reach subcutaneous layer. Sodium hyaluronate (NaHA), the sodium salt of hyaluronic acid, is a hydrophilic polysaccharide derivative polymer. It has ability to enhance percutaneous penetration by loosening the dense of the compact substance stratum corneum. The aim of this research was to observe the effects of NaHA on caffeine penetration as anticellulite active agent in three types of gel preparation: hydrogel, hydroalcoholic gel, and gel emulsion. Each gel type contained caffeine 1,5% and was varied into three formulas. Formula 1 contained HPMC 2% as gel basis; formula 2 contained HPMC 2% and NaHA 0,5%; formula 3 contained NaHA 2% as gel basis. Caffeine penetration properties were analyzed by Franz diffusion cell in vitro test using rat skin as membrane. Percent caffeine penetration of hydrogel formula 1, 2, 3 were 9,41 ± 0,01%; 11,74 ± 0,13%; 16,32 ± 0,03%, respectively. Percent caffeine penetration of hydroalcoholic gel formula 1, 2, 3 were 19,54 ± 0,02%; 22,99 ± 0,23%; 7,42 ± 0,08%, respectively. Percent caffeine penetration of gel emulsion formula 1, 2, 3 were 10,47 ± 0,19%; 13,41 ± 0,12%; 18,42 ± 0,06%, respectively. The result showed that NaHA enhanced the caffeine percutaneous penetration properties in various gel preparations, except hidroalkoholic gel formula 3.